Local perceptions and factors determining ecosystem services identification around two forest reserves in Northern Benin - Gerard N. Gouwakinnou; Séverin Biaou; Fifanou G. Vodouhe; Marc S. Tovihessi; Beranger K. Awessou; Honoré S. S. Biaou (BMC, 2019)
Abstract Background Ecosystems provide humanity with goods and services known as ecosystem services. The value of these services represents a basis for political decision-making. To be sure that these decisions are made on a valid basis, policymakers require an understanding of the biophysical processes involved. This study was carried out around two forest reserves (Alibori-Supérieur and Ouénou-Bénou) in Northern Benin. It aimed to highlight the knowledge of the surrounding communities and their perceptions about the importance of the ecosystem services provided by these forest reserves as well as the factors that influence their knowledge and perceptions. Methods Primary data were collected from 25 group discussions in 25 villages surrounding the forest reserves based on predefined ecosystems services of the Millennium Ecosystems Assessment (MA). Multiple linear regression models were used to examine how socio-economic characteristics of the communities influenced the ecosystem services identification rate. Perceptions of importance, levels of satisfaction, and trends of services provided were analyzed using descriptive statistics. Results Our results showed that education level, poverty index, household size, and proximity to forests played an important role in the variation in knowledge of ecosystem services (P < 0.05). Provisioning services (such as crops supply, fuelwood, lumber, wild food, and medicinal plants) were mostly identified by the poorest villages located very close to the forests (P < 0.05). The importance of the provided services for well-being has been unanimously recognized. The most recognized cultural services were education and knowledge facilitation (84%) and spiritual value (76%). Climate regulation (84%) and pollination (84%) were the best-known regulating services. However, supporting services (soil formation and pest regulation) that are important for improving production systems were unknown to the communities. Conclusion Education level, poverty index, and village proximity to the forest were important predictors of regulating and supporting services identification. But use of non-tangible services by local rural communities will require more emphasis on targeted environmental education specifically designed according to the needs of each group.